An Equivalence Theorem for the Core of an Economy Whose Atoms Are Not "Too" Big - Gabszewicz, Jean Jaskold; Mertens, Jean-Francois (Econometrica, 1971)
[This paper is a natural outgrowth of recent studies in markets with a "continuum" of traders. An equivalence theorem for the core of such economies was obtained, under the assumption that the measure space of economic agents is atomless. We introduce a sufficient condition under which the preceding result can be extended to economies containing "atomic" traders. The condition bears on the measure of the atoms.]